2020
DOI: 10.1007/s11427-020-1807-0
|View full text |Cite
|
Sign up to set email alerts
|

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication

Abstract: The Y chromosome plays key roles in male fertility and reflects the evolutionary history of paternal lineages. Here, we present a de novo genome assembly of the Hu sheep with the first draft assembly of ovine Y chromosome (oMSY), using nanopore sequencing and Hi-C technologies. The oMSY that we generated spans 10.6 Mb from which 775 Y-SNPs were identified by applying a large panel of whole genome sequences from worldwide sheep and wild Iranian mouflons. Three major paternal lineages (HY1a, HY1b and HY2) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 79 publications
3
48
0
Order By: Relevance
“…Then, we annotated 10 known single-copy genes ( AMELY , OFD1Y , USP9Y , ZRSR2Y, UTY , DDX3Y , ZFY , EIF2S3Y , SRY , and RMBY ) (Fig. 5 b) and three multi-copy gene families ( HSFY , ZNF280AY , and ZNF280BY ) by comparative gene annotation using Y chromosome genes from sheep [ 73 ] and cattle [ 74 ]. Furthermore, we searched all available published Capra Y-linked amplicons from the NCBI nucleotide database and found nine entries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we annotated 10 known single-copy genes ( AMELY , OFD1Y , USP9Y , ZRSR2Y, UTY , DDX3Y , ZFY , EIF2S3Y , SRY , and RMBY ) (Fig. 5 b) and three multi-copy gene families ( HSFY , ZNF280AY , and ZNF280BY ) by comparative gene annotation using Y chromosome genes from sheep [ 73 ] and cattle [ 74 ]. Furthermore, we searched all available published Capra Y-linked amplicons from the NCBI nucleotide database and found nine entries.…”
Section: Resultsmentioning
confidence: 99%
“…The single-copy region of the Y chromosome is conserved, especially among related species [ 25 ]. Thus, we used the BLAST-Like Alignment Tool (BLAT) [ 26 ] to extract scaffolds containing the ten Y chromosome-linked single-copy genes ( AMELY , OFD1Y , USP9Y , ZRSR2Y , UTY , DDX3Y , ZFY , EIF2S3Y , SRY , and RBMY ) in sheep [ 27 ] and found that one scaffold from the Flye version contains seven of these loci in the same order as on the ovine Y chromosome. We also show that the longest scaffold from Wtdbg2 only covers five of the mentioned single-copy genes, indicating that the Y chromosome-linked genes from Flye would be more continuous.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding of the complex process of sheep domestication has been greatly aided by the use of various molecular techniques, such as retrovirus integration analysis [182]; SNP analysis [183,184]; stable isotope analysis [185][186][187][188][189]; uni-parentally inherited DNA (mtDNA and Y-chromosomal DNA, both modern and ancient) (e.g., [190][191][192][193][194][195]); and, of late, large-scale genomic studies performed on modern samples [196][197][198][199][200] (Figures 1, 2 and 4). In addition, the differentiation from the morphologically similar goats (Capra hircus) has been facilitated by collagen-peptide mass fingerprinting [201,202] and recently published ancient mitogenomic sequences [203].…”
Section: Sheepmentioning
confidence: 99%
“…Analyses of uni-parentally inherited DNA sequences from modern [205][206][207][208][213][214][215][216] and ancient samples [194,210,212,217,218] have demonstrated the development of phylogeographic structure following domestication [197], possibly as a consequence of bottlenecks during migration. The clustering of both the deeply divergent rare Y-chromosomal haplotype (HY2) and the mitochondrial lineage C with Iranian mouflon, rather than with the wild mouflon from South East Anatolia, has been suggested to result from wild introgression [196,197], which has been proposed for other rare and geographically restricted mitochondrial lineages [196,197].…”
Section: Sheepmentioning
confidence: 99%
“…Since males play a more important role in the livestock mating system, it is expected that the reproduction performance of sheep will be improved through males by searching for effective Y chromosome molecular markers. Although the ovine Y chromosome has been sequenced and partly annotated (Li et al, 2021), the molecular characteristics and the function of ovine DDX3Y are largely unknown. It seems logical that variations in the Y‐chromosome will be correlated with male‐specific traits, but this has only been described sporadically, even in human genetics (Jobling & Tyler‐Smith, 2017; Yue et al, 2014).…”
Section: Introductionmentioning
confidence: 99%